PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR MATEMATIKA SISWA FASE F SMK N 6 PADANG - Natasya, Farra; Refnywidialistuti, Refnywidialistuti; Fitri, Yuliani (Ekasakti Educational Scientific Journal, 2024)
Mathematics teacher strive to make student interested in changing students perceptions of mathematics so that mathematics learning goals can be achieved. The research aims to compare learning outcomes, whether students mathematics learning outcomes by applying the Contextual Teaching and Learning (CTL) approach are better than students mathematics learning outcomes by applyimh conventional learning models in phase F class students at SMK N 6 Padang. Based on data analysis of students mathematics learning outcomes, it was found that students mathematics learning outcomes by applying the CTL approach tended to increase. Data on students mathematics learning outcomes in the experimental class sample is not normally distributed and the control class is normally distributed, has a homogeneuos variance. Because one of the samples was not normal a non parametric test was used using the Man-Whitney U test. After processing the data, it showed that the value was smaller than , so was accepted, it could be concluded that the learning outcomes using the CTL approach were batter than the learning outcomes using the CTL approach were better than the learning outcomes. Mathematics students who apply conventional learning to phase F students at SMK N 6 Padang.